Ekonomia rozwoju wobec problemów nędzy i nierówności społecznych na świecie - Piasecki, Ryszard (Annales. Etyka w Życiu Gospodarczym, 2008)
Development economics became a separate discipline in economic science in the 50s but only inthe 60s and mid-70s can one note a bigger interest in those issues. Gradually, there has appearedan extensive literature concerning economic development. In the 80s it turned out, however, that despitesome successes, the economic development of the majority of mid- and less developed countries wasless satisfactory than expected. During most of the 80s and 90s the so-called Washington consensusdominated theory and practice of economic development. This notion covered the whole range ofactivities that were to lead the developing countries to greater welfare and prosperity. It included toughfiscal and monetary policy, deregulation, foreign trade and capital flow liberalisation, elimination ofgovernment subsidies, moderate taxation, liberalisation of interest rates, maintaining low inflation,etc. From the developmental experience of the past years, a new developmental paradigm is emerging,the elements of which can be described in the following way:• basic economic environment should support investments in the long term• economy should be very sensitive to market stimuli• human resources should complement physical capital• information quick flow and absorption in the fast changing world attribute the key role tothe institutions and mechanisms which jointly react to the stimuli.• Wherever there are market imperfections, state intervention should be market friendly.• Social equality must be guaranteed if the economic development is supposed to last ona sustainable basis.